2000
DOI: 10.1063/1.126139
|View full text |Cite
|
Sign up to set email alerts
|

p-type doping with N and Li acceptors of ZnS grown by metalorganic vapor phase epitaxy

Abstract: Articles you may be interested inResidual and intentional n-type doping of ZnO thin films grown by metal-organic vapor phase epitaxy on sapphire and ZnO substrates Effects of substrate treatment and growth conditions on structure, morphology, and luminescence of homoepitaxial ZnTe deposited by metalorganic vapor phase epitaxy Control of conductivity type in undoped ZnO thin films grown by metalorganic vapor phase epitaxy J. Appl. Phys. 95, 6268 (2004); 10.1063/1.1713040Photoluminescence of iodine-doped ZnTe ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
31
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…In fact, it is probable that the only change in the donors is that they are more likely to be close to acceptors, because of the high N concentration, and thus will contribute to emission through a D 0 A 0 process, rather than an excitonic process. The position of the A 0 X line in the N-doped sample is a little below that in the undoped sample, but, interestingly, this is exactly what is seen in both ZnSe and ZnS doped with N. 21 The broad line centered at 3.238 eV in the N-doped sample is probably composed of two emissions: ͑1͒ an LOphonon replica of A 0 X and ͑2͒ D 0 A 0 recombination. The D 0 A 0 energy for a given pair will be given by E DA ϭE G ϪE D ϪE A ϩe 2 /4 r, where E G , E D , and E A are the band gap, donor, and acceptor energies, respectively, is the dielectric constant, and r is the pair separation.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…In fact, it is probable that the only change in the donors is that they are more likely to be close to acceptors, because of the high N concentration, and thus will contribute to emission through a D 0 A 0 process, rather than an excitonic process. The position of the A 0 X line in the N-doped sample is a little below that in the undoped sample, but, interestingly, this is exactly what is seen in both ZnSe and ZnS doped with N. 21 The broad line centered at 3.238 eV in the N-doped sample is probably composed of two emissions: ͑1͒ an LOphonon replica of A 0 X and ͑2͒ D 0 A 0 recombination. The D 0 A 0 energy for a given pair will be given by E DA ϭE G ϪE D ϪE A ϩe 2 /4 r, where E G , E D , and E A are the band gap, donor, and acceptor energies, respectively, is the dielectric constant, and r is the pair separation.…”
mentioning
confidence: 78%
“…The p-type films were grown on Li-doped, semiinsulating ZnO substrates 20 in order to be able to perform Hall-effect measurements without influence from substrate conduction. It is well known that N acts as a shallow acceptor in ZnSe and ZnS, 21 and it has also been employed in some of the other attempts to grow p-type ZnO. 3,5,6 Typical film thicknesses were 1-2 m, with the sample discussed here having a value of 1.9 m.…”
mentioning
confidence: 99%
“…However, it is very difficult to achieve p-type conduction in this material, and thus practical semiconductor devices have not been realized using ZnS-based materials. To date, there have been several reports on p-type conduction in ZnS, including ZnS:N [9] and ZnS:N,Ag,In [10] grown by vapor phase epitaxy, ZnS:Li grown by metal-organic vapor phase epitaxy (MOVPE) [11,12], ZnS:N and ZnS:Li grown by MOVPE [13]. However, there is no established and reproducible growth technique for the p-type ZnS with sufficiently low resistivity and good optical property.…”
mentioning
confidence: 98%
“…Hall-effect measurements at room temperature revealed free hole concentration and mobility values to be (0.56-1.4) Â 10 19 cm --3 and 11-25 cm 2 /Vs, respectively for ZnS : (Ag, In and N) [4]. On the other hand, Svob et al [5] have reported p-type ZnS : N with hole concentrations up to 10 18 cm --3 [5]. They found that the energy levels of the N acceptors are at about 0.19 eV above the valence band.…”
mentioning
confidence: 99%
“…Based on these two findings obtained by different groups [4,5], ZnS : (Ag, In and N) should be examined in terms of the effects of the reactive codopants, In donors, on the N-impurity states: The codoping method has been previously proposed by us [6][7][8].…”
mentioning
confidence: 99%